2021
DOI: 10.1002/ab.21955
|View full text |Cite
|
Sign up to set email alerts
|

Sexual violence victimization and suicide: Testing a coping‐mental health framework

Abstract: Sexual violence victimization is a prevalent public health concern. However, little research has investigated the factors linking sexual violence victimization to suicidal thoughts and behaviors (STBs). The current study tested the applicability of the psychological mediation framework, a coping‐mental health model, for the prevention of STBs among victims of sexual youviolence. Furthermore, the current study explored whether sexual orientation moderated the progression from sexual violence victimization to ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
3
1
0
Order By: Relevance
“…Furthermore, a direct and positive association between emotion dysregulation and controlling behaviors of isolation was found in accordance with H3, and the mediating role of emotion dysregulation in the relation between internalized homonegativity and isolating controlling behaviors was confirmed as well (H4). These findings confirm previous literature that found emotion dysregulation to be associated with IPV [ 77 , 78 , 79 , 80 ], supporting this relation in regard to isolating behaviors as well. In addition, our data support the application of the PMF [ 32 ] to SSIPV perpetration.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, a direct and positive association between emotion dysregulation and controlling behaviors of isolation was found in accordance with H3, and the mediating role of emotion dysregulation in the relation between internalized homonegativity and isolating controlling behaviors was confirmed as well (H4). These findings confirm previous literature that found emotion dysregulation to be associated with IPV [ 77 , 78 , 79 , 80 ], supporting this relation in regard to isolating behaviors as well. In addition, our data support the application of the PMF [ 32 ] to SSIPV perpetration.…”
Section: Discussionsupporting
confidence: 92%
“…The results, with more than a threefold proportion exposed to penetrative sexual violence who had or had been diagnosed with depression, anxiety or fatigue syndrome compared with not exposed, are in line with previous Swedish and international studies 7–9,14 . The fact that the proportion with suicide attempts is so high among participants exposed to sexual violence compared to unexposed is in line with both international studies and experience from WONSA's specialist clinic, where 38% of patients had made at least one suicide attempt, and 25% had made two or more suicide attempts 10,15 . This is also in line with results from a study on young people in the Stockholm Region, where a 26‐fold increased risk of seeking medical care due to suicide attempts was seen after a sexual assault had been registered in the medical record, compared with girls of the same age in the same residential area without such registration in the journal 9 .…”
Section: Discussionsupporting
confidence: 89%
“…[7][8][9]14 The fact that the proportion with suicide attempts is so high among participants exposed to sexual violence compared to unexposed is in line with both international studies and experience from WONSA's specialist clinic, where 38% of patients had made at least one suicide attempt, and 25% had made two or more suicide attempts. 10,15 This is also in line with results from a study on young people in the Stockholm Region, where a 26-fold increased risk of seeking medical care due to suicide attempts was seen after a sexual assault had been registered in the medical record, compared with girls of the same age in the same residential area without such registration in the journal. 9 The similarity regarding suicidality between the findings from consecutive patients at the WONSA clinic, the register-based study and in the present online survey study suggest, that the survey had fairly good validity.…”
Section: Discussionsupporting
confidence: 83%
“…Nonetheless, tendencies to use cognitive reappraisal to regulate emotions appear to buffer the effects of stress on SI and NSSI, which may be particularly important for groups who experience elevated rates of stressful life events. Indeed, one study found that the negative association between cognitive reappraisal and SITB was stronger for sexual minorities compared to heterosexual participants (Kaniuka et al, 2021). Therefore, cognitive reappraisal may be particularly helpful for certain marginalized populations.…”
Section: Resultsmentioning
confidence: 99%